Effects of exposure to sexually explicit material on sexually violent behavior among first-year university men in Vietnam. - Irina Bergenfeld; Yuk Fai Cheong; Tran Hung Minh; Quach Thu Trang; Kathryn M Yount (PLoS ONE, 2022)
Background Adolescence and emerging adulthood represent a period of heightened vulnerability to sexual violence (SV). While some research suggests that exposure to sexually explicit material (SEM) among adolescents and college students is associated with sexually violent behavior, our understanding of this relationship is limited. This study aimed to assess the relationship between prior exposure to several types of SEM and sexually violent behavior in a sample of first-year university men in Vietnam. Methods and findings A cohort of 739 first-year male university students completed three survey waves over 14 months, providing information on contact and non-contact sexually violent behavior, exposure to SEM, and other theorized confounders of the SEM-SV relationship. Controlling for these covariates, we estimated the average treatment effect of SEM on contact and non-contact SV using the propensity score method. We also conducted a dose-response analysis for the effect of violent SEM on SV based on frequency-of-exposure classes derived from latent class analysis. The majority of the sample reported exposure to SEM in the prior six months, with 41% of the sample reporting exposure to violent SEM. In propensity-adjusted models, exposure to violent SEM, but not other types, had a small but significant positive effect on contact and non-contact SV. These effects increased for frequent viewers of violent SEM. Models of contact SV showed endogeneity, warranting caution. Conclusions Exposure to violent SEM is prevalent among university men in Vietnam and may be contributing to sexually violent behavior. Incorporating media literacy into SV prevention programs to mitigate these potential effects may be warranted.